Annual Variation in Atmospheric 14C Between 1700 BC and 1480 BC. Issue 4 (6th August 2020) - Pearson, Charlotte; Wacker, Lukas; Bayliss, Alex; Brown, David; Salzer, Matthew; Brewer, Peter; Bollhalder, Silvia; Boswijk, Gretel; Hodgins, Gregory
ABSTRACT: In 2018 Pearson et al. published a new sequence of annual radiocarbon ( 14 C) data derived from oak ( Quercus sp.) trees from Northern Ireland and bristlecone pine ( Pinus longaeva ) from North America across the period 1700–1500 BC. The study indicated that the more highly resolved shape of an annually based calibration dataset could improve the accuracy of 14 C calibration during this period. This finding had implications for the controversial dating of the eruption of Thera in the Eastern Mediterranean. To test for interlaboratory variation and improve the robustness of the annual dataset for calibration purposes, we have generated a replicate sequence from the same Irish oaks at ETH Zürich. These data are compatible with the Irish oak 14 C dataset previously produced at the University of Arizona and are used (along with additional data) to examine inter-tree and interlaboratory variation in multiyear annual 14 C time-series. The results raise questions about regional 14 C offsets at different scales and demonstrate the potential of annually resolved 14 C for refining subdecadal and larger scale features for calibration, solar reconstruction, and multiproxy synchronization.